Analisis Semiotika pada Desain Kemasan “Air Alam” - Khozinatus Sadah; Agus Wibowo; Muhammad Turmudzi (Universitas Sains dan Teknologi Komputer, 2025)
Technological developments and creativity have resulted in a wide variety of rapidly evolving packaging designs. One of humanity's basic needs is the fulfillment of drinking water requirements. In the past, people obtained drinking water from the nearest source and then processed (boiled) it. However, today this need is met by drinking water companies. One drinking water manufacturer with unique packaging design is AirAlam. This product has packaging that is different from other products. While most product packaging generally features icons of mountains, water, nature, and logos that clarify the product brand, AirAlam's product highlights a map of Indonesia with details in the form of parang batik motifs. This study will focus on analyzing the design elements of AirAlam's product packaging. The purpose of this study is to obtain information from the visual meaning displayed on AirAlam product packaging. This study uses a qualitative descriptive method, with a semiotic approach from Charles Sanders Peirce and Rolland Barthes. The results of the analysis show that the AirAlam packaging design conveys an image of local authenticity, love for Indonesian products, purity, and environmental sustainability. Local authenticity and love for Indonesian products are represented by a map of Indonesia with batik details. Purity is represented by packaging design that has no background (clear) and the use of a single white color in the packaging design. Meanwhile, sustainability is represented by the use of recyclable materials.